Shield of sparrows [large type] - Perry, Devney (Thorndike Press large print dynamic drama., 2025)
The gods sent monsters to the five kingdoms to remind mortals they must kneel. I've spent my life kneeling--to their will and to my father's. As a princess, my duty is to wear the crown and obey the king. I was never meant to rule or fight--or seal an ancient treaty with my own blood. But one fateful day a legendary monster hunter sailed to our shores, and a prince ruined my life. Now I'm crossing treacherous lands beside a warrior who despises me as much as I despise him--bound to a future I ddin't choose and a husband I barely know. Everyone wants me to be something I'm not--a queen, a spy, a sacrifice. But what if I refused this role and made my own rules? And what if--for the first time--I reached for power?